Visible implant alphanumeric (VIA) as a marking method in the lesser snouted treefrog scinax nasicus - Caballero Gini, Andrea Natalia (2019)
In this study we assessed the efficacy of Visible Implant Alphanumeric (VIA) for marking adults and juveniles of the Neotropical treefrog Scinax nasicus. We evaluated the success of this technique in the identification of individuals and the prevalence of tags in the field. As a control, we marked the same individuals through toe-clipping. Of 196 marked individuals, 57 were recaptured in a 7-month study period. Only one mark was unreadable because it was located too deep in the skin. We found one case of tag expulsion and two inverted tags. Almost complete regeneration of the adhesive disk was observed by the fifth month of the study in all recaptured frogs. We suggest VIA tagging method as suitable for S. nasicus over long term studies. Even though, a hybrid method for marking (VIA + toe-clipping) is recommended for species with dark and/or loose skin, or large frogs.